Formação de professores em processos andragógicos de ensino e aprendizagem - Dagostino, Glaucia Berton (2011)
The formation of professors for teaching and acting specifically with adults, has a direct relation with the necessity to establish and clarify the way adults learn, which is different from the children process of learning, therefore, to study this subject, it was required to explore the field of Andragogy. Over time, education beyond the school walls, has been employed in various fields of society. In this sense, the term Andragogy began to be adopted regarding the educational processes and education for adults, differing from the pedagogy that concentrates its efforts on issues related to education of children. Given the matters presented, we tried to focus the research on something specific and of greater relevance to the Education sector, since the Andragogy is a subject with few studies in Brazil. We decided then to study, analyze and indicate the importance of the teacher training for professors who work specifically with adults. Thus, the research problem was presented: What is the knowledge necessary to train teachers in andragogical involvement in cases of teaching and learning? It was performed a bibliographic research in order to develop a detailed theoretical work on this subject. The survey instrument used was bibliographic work on the subject studied. After the research, it was concluded that teacher knowledge that professors who work with adults need to have must be based on the categories andragogical identified throughout this study, which are: interaction, planning, adoption of a methodology focused on learning, work with a focus on memory in identity construction of the subject, considering the subjectivity in the process of adult education and discover how students learn through metacognition. According to the bibliography studied and thought about learning the features that stood out the most when dealing with the adult learning are the aspects related to life time experiences, and prior knowledge they bring when they are embedded in a learning environment and that can not be brushed aside by the teacher